The Difference in Speed Sequence Influences Perceived Duration. (February 2013) - Sasaki, Kyoshiro; Yamamoto, Kentaro; Miura, Kayo
Perceived duration of a moving stimulus increases with the speed of the motion. However, a recent study found that the perceived duration of a decelerating stimulus was longer than that of an accelerating one, even though their averaged speed was identical (Matthews 2011 Journal of Experimental Psychology: Human Perception and Performance 37 1617–1627). We conducted three experiments to discover how this speed-change-induced time distortion occurs. We found that the perceived duration of a decelerating motion was longer than that of an accelerating one both in sub-second and supra-second presentation duration conditions, when speed changed linearly over time (experiment 1). The differences could not be explained by the differences in average perceived speed between them (experiment 2). Moreover, the perceived duration of a decelerating motion was also longer than that of an accelerating one, even when speed changed once during the presentation duration (experiment 3). These results suggest that average speed differences in the early and late parts of the presentation duration are important for the occurrence of the speed-change-induced time distortion.